The negative impact of subsidies on the adoption of drip irrigation in India: evidence from Madhya Pradesh - Malik, Ravinder Paul Singh; Giordano, Mark; Rathore, M.S. (Informa UK Limited, 2018)
Drip irrigation in India has expanded slowly. One reason cited is the high capital costs facing the smallholder-dominated agricultural sector. Governments have provided capital subsidies in response. This study finds that, rather than improving access to drip, the subsidy system holds the technology back, because its technical requirements, highly bureaucratic processes and pricing incentives turn many drip providers into rent-seeking agents rather than service providers to farmers, leading to price increases of 40% or more. If capital costs are truly the constraint on drip expansion in India, alternative models to address them are available.